Skill Bias Magnified: Intersectoral Linkages and White-Collar Labor Demand in U.S. Manufacturing - Voigtländer, Nico (The Review of Economics and Statistics, 2014)
This paper presents a novel stylized fact and analyzes its contribution to the skill bias of technical change in U.S. manufacturing. The share of skilled labor embedded in intermediate inputs correlates strongly with the skill share employed in final production. This finding points towards an intersectoral technology-skill complementarity (ITSC). Together with input-output linkages, the observed complementarity delivers a multiplier that reinforces skill demand along the production chain. Reduced-form estimates suggest that the effect is quantitatively important, explaining about as much skill upgrading as outsourcing. Empirical evidence suggests that one channel through which this complementarity works is product innovation. I also analyze the importance of different drivers of skill upgrading over time. While foreign outsourcing and IT capital is associated with skill demand particularly strongly from the 1980s onwards (a period of rapidly increasing skill premia), R&D contributed stably throughout the period 1958-2005. The same is true for ITSC, which augmented within-sector skill bias in a stable fashion throughout the last 5 decades.